Improving Students’ Speaking Skills Through Project-Based English Health Promotion Activities - Fitri Harahap; Izzati Suhaila; Lastri Marsely Ginting; Butet Marthalina Saragih (Journal of Applied Linguistics, 2026)
This study aimed to examine the effectiveness of Project-Based English Health Promotion Activities in improving students’ speaking skills. The study used a quasi-experimental design with two groups : a control group taught using conventional methods and an experimental group taught using project-based learning. The participants were 50 fourth-semester undergraduate Public Health students, divided into two classes of 25 students each. Students’ speaking skills were assessed through a pre-test and post-test focusing on fluency, accuracy, pronunciation, vocabulary, and confidence. The data were analyzed using t-tests. The results showed that both groups improved their speaking skills, but the experimental group achieved significantly higher improvement than the control group (p < 0.05). The study concludes that Project-Based English Health Promotion Activities are effective in enhancing students’ speaking skills and can be applied in English for Specific Purposes (ESP) instruction, particularly in health-related programs. Keywords : Improving; Speaking Skills; Project Based English; Health Promotion